Changes in smoking patterns after HIV diagnosis or antiretroviral treatment initiation: a global systematic review and meta-analysis - Jobert Richie Nansseu; Dalhia Noelle Tounouga; Jean Jacques Noubiap; Jean Joel Bigna (BMC, 2020)
Abstract Background Tobacco consumption is more life-threatening in people living with human immunodeficiency virus (HIV) than within the general population; therefore, people living with HIV (PLWH) should be highly motivated to take action towards quitting smoking at or after HIV diagnosis. The aim of this systematic review with meta-analysis was to investigate changes in smoking habits among PLWH over time. Main text We considered prospective and retrospective cohort studies including PLWH aged 15 years and above, which have measured the prevalence of tobacco smoking (current, former or never) at study initiation and completion, and published between January 1, 2000 and April 15, 2018 without language or geographical restriction. We searched PubMed, EMBASE, Web of Science, Africa Journal Online, and Global Index Medicus. We used a random-effects model to pool data. Nine studies were included. The proportion of current and former smokers decreased slightly over time, around 2.5 and 3.8%, respectively. However, the proportion of never smokers decreased sharply by 22.5%, and there were 2.1 and 1.5% PLWH who shifted from never and former smoking to current smoking, respectively. On the other hand, 10.5% PLWH shifted from current to former smoking, 7.1% tried to quit tobacco consumption but failed, and 10.1% stayed in the "never smoking" category over time. Conclusions PLWH seem not to change positively their smoking habits towards quitting tobacco consumption. There is urgent need to increase actions aimed at helping this vulnerable population to quit tobacco consumption, including individually tailored therapeutic education, psychosocial and pharmacologic supports.